Preoperative atrial fibrillation is an independent predictor of worse early and late outcomes after isolated coronary artery bypass graft surgery. Issue 3 (March 2015) - Saxena, Akshat; Kapoor, Jada; Dinh, Diem T.; Smith, Julian A.; Shardey, Gilbert C.; Newcomb, Andrew E.
Abstract: Objectives: To evaluate the impact of preoperative atrial fibrillation (pre-op AF) on early and late mortality after isolated coronary artery bypass graft (CABG) surgery. Methods: Data obtained prospectively between June 2001 and December 2009 by the Australasian Society of Cardiac and Thoracic Surgeons National Cardiac Surgery Database Program were retrospectively analyzed. Patients who underwent concomitant atrial arrhythmia surgery/ablation were excluded. Demographic and operative data were compared between patients with and without pre-op AF. The independent association of pre-op AF on early mortality, perioperative complications, and late mortality was determined. Results: Isolated CABG surgery was performed in 21, 534 patients; 1312 (6.1%) presented with pre-op AF. Pre-op AF patients were older (mean age, 71 years vs. 65 years, p < 0.001) and had more comorbidities reflected in a higher additive EuroSCORE (8.4 ± 3.5 vs. 6.5 ± 3.2, p = 0.001). Even after accounting for confounding factors, however, pre-op AF was associated with a 63% increase in 30-day mortality [4.2% vs. 1.4%; hazard ratio (HR), 1.63; 95% confidence interval (CI), 1.17–2.29; p = 0.004] and 39% increase in late mortality (5-year survival, 78% vs. 90%; HR, 1.39; 95% CI, 1.20–1.61; p < 0.001). Conclusion: Pre-op AF is an independent predictor of poor early and late outcomes. Pre-op AF should be considered, therefore, in the development or update of risk stratification models for CABG surgery.